SEJARAH PEMBERONTAKAN GERAKAN ACEH MERDEKA (GAM) DI ACEH TAHUN 1976-2005 - Murni Wahyuni Murni Wahyuni; Isjoni Isjoni '; Bedriati Ibrahim Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Free Aceh Movement declared by Hasan Tiro in 1976 is a form of frustration caused by the central government that adopts centralism. Not only that, Aceh also support Indonesia's struggle against the Dutch in order to maintain independence. Aceh also contributed a substantial contribution, even called the capital region of the Republic of Indonesia by Soekarno. The purpose of this study was to determine the state of Aceh prior to the uprising Aceh Movement, to determine the causes of the uprising Aceh Movement, to determine the Free Aceh Movement rebellion in 1976-2005, to know what are the government's efforts to quell the rebellion of the Free Aceh Movement and to know the state of Aceh after the holding of the peace agreement. The method used is the historical method in which data are collected through Library Studies, Interviews and Documentation. Analysis of the data using the method of writing history. When the study began filing title until the completion of a revised proposal last essay writer. The results showed that, economic, cultural and disappointment Aceh had been the cause of the rebellion. In a further development deadly unrest mainly civilians. Furthermore, each president has their own way to quell the revolt. The final stage of the insurgency is a peace agreement or memorandum of understanding signed in Helsinki with a long debate agreed by both parties in 2005. In addition, the tsunami disaster also had a hand in this peacekeeping because it is considered as the driving force of the peace plan. Based on these results it can be concluded that the 29-year insurgency in Aceh to achieve justice is expected to be met with the Memorandum of Understanding.Keywords: History, Rebellion, Free Aceh Movement